Improving Students' Mathematical Problem-Solving Ability through the Use of External Representations - Amirul Syah; Harizahayu Harizahayu; Annisah Annisah; Emy Yunita Rahma Pratiwi; Gamar Al Haddar (Journal on Education, 2023)
This study has the objectives, namely first, to find out whether students' mathematical problem-solving abilities can be improved by using external representations. Second, analyzing student activities in learning mathematics by using external representations. Third, analyzing student responses to learning mathematics by using external representations. This research uses classroom action research (CAR) or classroom action testing (PTK) methods. According to O'Brien in Mulyatiningsih, "action research is carried out when a group of people (students) identify the problem, then the researcher determines an action to overcome it." Classroom Action Research (CAR) seeks to develop and reflect on a learning model with the aim of improving learning processes and outcomes. Based on the results of the research, it can be concluded that: learning using external representations can improve mathematical problem solving abilities; it can be seen that there is an increase in the number of students who score above the KKM in cycle II, with the percentage of students who are declared complete (reaching the KKM) at 71.4%, or as many as 20 students are higher than in cycle I, with a percentage of 53.57%, or as many as 15 students who are declared complete. This means that most students have achieved learning mastery resulting from learning through the use of external representations